Plan de mejora para la bodega de publicidad de la empresa Postobón S.A Sede Bello. - Silva Márquez, Juan Felipe; Barrios Escobar, Luis Francisco; Feris López, Salim Antonio (Corporación Universitaria Minuto de Dios, 2017)
Este trabajo pretende orientar a la organización Postobón S.A. sede Bello en cuanto al manejo del inventario de insumos para publicidad, mostrando con teoría y pruebas de campo la importancia de esto, lo cual traerá consigo beneficios para la organización.

This work aims to guide Postobón S.A headquarters Bello organization in managing the inventory of supplies for advertising, showing theory and field tests the importance of this, which will bring benefits to the organization. In the inventory and warehouse management process, there are a series of opportunities that, when exploited in an efficient manner, could lead the company to other levels of competitiveness and customer satisfaction. Postobón S.A headquarters Bello, presents an opportunity for improvement in the management of advertising supplies stored in their facilities nowayadays, because there is no control of what is stored there, which is causing delays in the processes of picking, shipments, and inventory control that will ultimately be reflected in the promise of service offered by Postobón S.A. The objective of this work is to develop a series of strategies that generally eliminate the uncertainty with which today operates the cellar of inputs for advertising, in particular and based on the theory studied for the realization of this work and the evidence obtained through the Surveys carried out and the subsequent analysis of the data obtained, will be proposed improvements to the processes carried out in said warehouse, such as: inventory systems A, B, C - Lean manufacturing - PHVA cycles, among others. The proposals made point to the optimization of time and resources with which today counts on the store of inputs for advertising Postobón S.A. company Bello.
Keywords: Administración industrial; Organización industrial; Logística en los negocios; Control de inventarios; Administración de materiales; Company; Enterprise Resource Planning; Lean Manufacturing